Smoking estimates from around the world: data from the first 17 participating countries in the World Mental Health Survey Consortium - Storr, Carla L (2009)
OBJECTIVE: To contribute new multinational findings on basic descriptive features of smoking and cessation, based upon standardised community surveys of adults residing in seven low-income and middle-income countries and 10 higher-income countries from all regions of the world. METHODS: Data were collected using standardised interviews and community probability sample survey methods conducted as part of the WHO World Mental Health Surveys Initiative. Demographic and socioeconomic correlates of smoking are studied using cross-tabulation and logistic regression approaches. Within-country sample weights were applied with variance estimation appropriate for complex sample survey designs. RESULTS: Estimated prevalence of smoking experience (history of ever smoking) and current smoking varied across the countries under study. In all but four countries, one out of every four adults currently smoked. In higher-income countries, estimated proportions of former smokers (those who had quit) were roughly double the corresponding estimates for most low-income and middle-income countries. Characteristics of smokers varied within individual countries, and in relation to the World Bank's low-medium-high gradient of economic development. In stark contrast to a sturdy male-female difference in the uptake of smoking seen in each country, there is no consistent sex-associated pattern in the odds of remaining a smoker (versus quitting). CONCLUSION: The World Mental Health Surveys estimates complement existing global tobacco monitoring efforts. The observed global diversity of associations with smoking and smoking cessation underscore reasons for implementation of the Framework Convention on Tobacco Control provisions and prompt local adaptation of prevention and control interventions.